2001
DOI: 10.1007/3-540-45574-4_12
|View full text |Cite
|
Sign up to set email alerts
|

Improving Locality for Adaptive Irregular Scientific Codes

Abstract: An important class of scientific codes access memory in an irregular manner. Because irregular access patterns reduce temporal and spatial locality, they tend to underutilize caches, resulting in poor performance. Researchers have shown that consecutively packing data relative to traversal order can significantly reduce cache miss rates by increasing spatial locality. In this paper, we investigate techniques for using partitioning algorithms to improve locality in adaptive irregular codes. We develop parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…To deal with this, the partitioner follows up the inflation step with a hierarchical partition joining step similar to GPart [7]. This phase is expressed in pseudocode in Figure 4.…”
Section: Description Of the Join Phasementioning
confidence: 99%
See 1 more Smart Citation
“…To deal with this, the partitioner follows up the inflation step with a hierarchical partition joining step similar to GPart [7]. This phase is expressed in pseudocode in Figure 4.…”
Section: Description Of the Join Phasementioning
confidence: 99%
“…GPart [7] is a hierarchical clustering partitioner that is significantly faster than METIS, but to the best of our knowledge it has not been parallelized. Its use has focused more on data reordering to improve locality [6] and it has features that allow the partitioning to target multiple levels of cache.…”
Section: Hierarchical Clustering or Growth Based Partitionersmentioning
confidence: 99%
“…On the other hand, temporal locality can only be improved by reordering the memory accesses so that the same addresses are accessed closer together. Advanced compiler methods to do this all target specific code patterns such as affine array expressions in regular loop nests [11,18,22], or specific sparse matrix computations [14,15,24,27]. For more general program constructs, fully-automatic optimization seems to be very hard, mainly due to the difficulty of the required dependence analysis.…”
Section: Related Workmentioning
confidence: 99%
“…Al-Furaih and Ranka examined graph-based clustering of irregular data for cache [3]. Other models include consecutive packing by Ding and Kennedy [10], space-filling curve by MellorCrummey et al [25], graph partitioning by Han and Tseng [17], and bucket sorting by Michell et al [26]. Several studies found that consecutive packing compared favorably with other models [25,31].…”
Section: Structure Splittingmentioning
confidence: 99%